Analisa Risiko Pembangunan Perumahan Jl Golf Kecamatan Liang Anggang Kota Banjarbaru (Studi Kasus: Perumahan PT Borneo Group) - Abdul Karim (Jurnal Teknologi Berkelanjutan, 2023)
In housing development, it is necessary to know that construction risks are likely to occur and have an impact on housing development. So the need for risk identification and risk mitigation to avoid and eliminate risks that fall into the dominant risk category. This study in the selection of respondents based on purposive sampling method and selected respondents who have competence and have work experience in the field of construction implementation. Based on the results of the research, the number of risks in housing development is 12 risks in housing development, namely political factors, economic factors, natural and environmental factors, technical factors, human factors, and security and safety factors which are also known in the level of risk to frequency, namely 1 Very Rarely, 2 Rarely, 6 Sometimes, 3 Often. Risk level for impact 4 very small, 8 medium. The qualitative risk level is 4 Low Risk, 2 Medium Risk and 6 High Risk. The level of risk acceptance is 6 undesirable and 6 acceptable risk. Risk mitigation is only carried out on dominant risks, namely 5 risks that are undesirable.